Comparison of changes in sugar contents in the cotyledons of radish and lablab - Tiwari, Shweta; Sharma, K (Recent Research in Science and Technology, 2012)
Seed germination is one of the most important phases in the life cycle of plants. Starch is the major stored reserve in both Radish and Lablab cotyledons. Most of such work is done in cereal grains might be due to advantages inherent with cereals which ensure easy manipulation of the system. However the work done so far with facts does open up some interesting possibilities of regulation of stored resources. The sugar level decreases to 29% from 96 to 120 hrs after imbibitions in case of Radish. In case of Lablab The sugar level decreases to 60% from 72 to 96 hrs after imbibitions. The decrement still continues from 96 to 120 hrs and the value is about 24%.